Two new eudesmanolides from sphaeranthus indicus (Linn) - Jadhav, Ravindra B.; Sonawane, Kiran B.; Deshpande, Nirmala R.; Rojatkar, Supada R. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2007)
Two new eudesmanolides have been isolated from the aerial part of Sphaeranthus indicus and their structures have been established as 11 alpha,13-dihydro-3 alpha,7 alpha-dihydroxyeudesm-4-en 6 alpha, 12-olide 1, 4-en-6 beta,7 alpha-eudesmanolide 3, on the basis of spectral data and comparison of spectral data with those of reported data of compounds 2, 4 and 5.
Keywords: eudesmanolides; olide; Sphaeranthus indicus

Efficacy of 4-methyl-7-hydroxy coumarin derivatives against vectors aedes aegypti and culex quinquefasciatus - Deshmukh, Madhavi; Pawar, Pushpa; Joseph, Mary P.; Phalgune, Usha; Kashalkar, Rajashree; Deshpande, Nirmala R. (Indian Journal of Experimental Biology, 2008)
4-Methyl-7-hydroxy coumarin is considered as a lead molecule as a biopesticide. Its mono bromo and tribromo derivatives were synthesized. Two more derivatives were synthesized by acylation. Compound 1 (3.6,8-tribromo-7-hydroxy-4-methyl-chromen-2-one) was found to be the most potent against IV(th) instar larvae of C. quinquefasciatus and A. aegypti the LC(50) being 1.49 and 2.23 ppm respectively. It showed 100% larval mortality at 25 ppm against A. aegypti and at 10 ppm against C. quinquefasciatus. Compounds 1 and 2 (3,6,8-tribromo-7-hydroxy-4-methyl-chromen-2'-oxo-2H-chromen-7-yl acetate) showed remarkable ovicidal activity. Significant reduction of 80-85%, hatching of eggs of both mosquito species was observed at the highest dose of 100 ppm. The hatched larvae showed 100% mortality in the successive instars. Compounds 3 and 4 (3-bromo-7-hydroxy-4-methyl-chromen-2-one and 3-bromo-4-methyl-2'-oxo-2H-chromen-7-yl acetate) showed moderate activity against both mosquito species.
Keywords: 4-Methyl-7-hydroxy coumarin; Aedes aegypti; Culex quinquefasciatus; Larval mortality; Ovicidal activity

Phytochemical investigation of artemisia pallens - Ruikar, Anjali D.; Jadhav, Ravindra B.; Phalgune, Usha D.; Rojatkar, Supada R.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Helvetica Chimica Acta, 2011)
Two new eudesmanolides, pallensin (1) and 4-epipallensin (2), along with a known eudesmanolide, santonin, and a known flavone, 4-epivalgarin, have been isolated from the aerial part of A. pallens. Their structures were established by detailed spectral studies (1D and 2D) and by comparison of their spectroscopic data with those of known compounds.

Sesquiterpene lactone, a potent drug molecule from artemisia pallens wall with anti-inflammatory activity - Ruikar, Anjali D.; Misar, Ashwini V.; Jadhav, Ravindra B.; Rojatkar, Supada R.; Mujumdar, Arvind M.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Arzneimittel-Forschung-Drug Research, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53-86-1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79 degrees. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pollens; Asteraceae; Mice; Single crystal x-ray structure

Larvicidal potential of mimusops elengi against aedes aegypti (L) and Culex quinquefasciatus (Say) - Ruikar, Anjali D.; Pawar, Pushpa V.; Sen, Avalokiteswar; Phalgune, Usha D.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Journal of Vector Borne Diseases, 2012)
Keywords: Aedes aegypti; Culex quinquefasciatus; larvicidal activity; Mimusops elengi

Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1